CITRA ANTIKOLONIAL DALAM FILM AVATAR (2009): SEBUAH TINJAUAN POSKOLONIAL - Eggy F Andalas (Puitika)
This study aims to explain the discourse revealed by James Cameron in Avatar movie (2009). This study uses Edward Said’s framework to answer the problem above. This study uses qualitative approach with descriptive design. The data source of this study is Avatar movie (2009) by James Cameron. The technique of data collection is done by doing the strategy of contrapuntal reading. The techniques of data analysis are done by some steps as follows: First, watching the movie for many times until the writer gets the comprehensive understanding. Second, writing the narration and the event down to show the problem about colonization in the movie. Third, observing every problem with using Edward Said’s framework. Fourth, presenting the result of the analysis. The result of this study shows that James Cameron reveals anti-colonial discourse which is opposite with the West’s image that used to be known as the subject. Furthermore, he also strongly criticizes the issue of the environment, the arrogance of the West and the colonization towards another nation through this movie.